Impact of supportive supervision visits on the availability of World Health Organization infection prevention and control core components in health facilities in Southwestern Uganda - Cozie Gwaikolo; Bongomin Bodo; Doreen Nabawanuka; Michael Mukiibi; Emmanuel Seremba; Paul Muyinda; Andrew Bakainaga; Yonas Tegegn Woldemariam; Christopher C. Moore; Richard Ssekitoleko (Elsevier, 2024)
Summary: Background: In sub-Saharan Africa, the provision of infection prevention and control (IPC) measures are often limited by resource constraints. Aim: To determine the association of supportive supervision activities with the availability of the WHO core components for IPC at health facilities in Southwestern Uganda. Methods: We employed a before and after quality improvement study design. We conducted a baseline assessment of the availability of the WHO IPC core components and provided supportive supervision activities, which was followed by a second IPC assessment. We included health centers II-IV, which have increasing clinical care capacity, and regional hospitals. Findings: Of 244 regional health facilities, baseline assessment occurred at 111 (45%) of which 23 (21%) were reassessed. The number of facilities in the Red (<70%) category for each core component stayed the same or decreased at each facility type, but there was an increase from five to six health center III facilities scoring Red (<70%) for PPE. The number of facilities in the Green (>85%) category for each core component stayed the same or was increased at each facility type, but there was a decrease from four to two health center III facilities scoring Green (>85%) for instrument processing. There was an increase in the median (interquartile range [IQR]) overall score for all facilities (65 [54-72] vs 75 [68-83], P=0.0001). Conclusion: Supportive supervision activities were associated with improved availability of the core components of IPC at health facilities in Southwestern Uganda. PPE should be prioritized in health care facilities in Southwestern Uganda.